Development of Coconut Palm Wood Seasoning Schedules - Mukundan, Gayathri; Anoop, E. V.; Chathoth, Anish Mavila; Shibu, Comath (International Coconut Community, 2024)
Coconut palm is a versatile and commercially important palm in the tropical and sub-tropical regions. This study attempts to standardise moisture content-based kiln seasoning schedules for high-density and medium-densitycoconut palm wood and also understand relationship between Pilodyn Penetration Depth (PPD) and basic density for three density classes (high, medium and low). Quick drying test was conducted to study the degree and type of drying defects viz., surface cracking, end splitting, honeycombing and deformation. Defects were graded according to the Terasawa (1965) scale. The baseline parameters such as initial dry bulb temperature, final dry bulb temperature and the wet bulb depression for high and medium-density coconut palm wood were chosen by considering the major seasoning defects. The samples were subjected to different seasoning schedule treatments in a convection kiln to determine the best treatment based on grading of defects. The ideal drying period obtained for high-density coconut palm wood was 11 days, whereas for medium-density coconut palm wood it was 12 days. The schedule developed has good potential for industrial application in seasoning of coconut palm wood lumber with reduced defects in coconut growing regions of the world. Keywords: Coconut palm wood, seasoning schedule, kiln drying, Terasawa scale